Exploitation of Key Regulatory Modules and Genes for High-Salt Adaptation in Schizothoracine by Weighted Gene Co-Expression Network Analysis - Luo Lei; Xingxing Deng; Fei Liu; He Gao; Yuting Duan; Junting Li; Suxing Fu; Hejiao Li; Yinhua Zhou; Rongrong Liao; Haiping Liu; Chaowei Zhou (Animals)
Schizothoracine fishes in saltwater lakes of the Tibetan Plateau are important models for studying the evolution and uplift of the Tibetan Plateau. Examining their adaptation to the high-salt environment is interesting. In this study, we first assembled the RNA-Seq data of each tissue of G. przewalskii, G. selincuoensis, and G. namensis from Qinghai Lake, Selincuo Lake, and Namtso Lake, respectively, obtained by the group previously. After obtaining reliable results, the adaptation of the gills, kidneys, and livers of the three species to the high-salinity environment was assessed by weighted gene co-expression network analysis (WGCNA). Using module eigengenes (ME), 21, 22, and 22 gene modules were identified for G. przewalskii, G. selincuoensis, and G. nemesis, respectively. Functional clustering analysis of genes in the significant association module identified several genes associated with osmolarity-regulated potential KEGG pathways in the gills of three species of Schizothoracine fish. Th17 cell differentiation pathway was up-regulated in the gills of all three species; histocompatibility class 2 II antigen and E alpha (h2-ea) were up-regulated genes in this pathway. Functional clustering analysis of genes in apparently related modules in the kidney unveiled several differential KEGG pathways. The pentose phosphate pathway was up-regulated in the three Schizothoracine fishes, and glucose-6-phosphate dehydrogenase (g6pd) was an up-regulated gene in this pathway. In the livers of the three Schizothorax species, the propanoate metabolism pathway was up-regulated, and succinate-CoA ligase GDP-forming subunit beta (suclg2) was an up-regulated gene in this pathway. The above analyses provide reference data for the adaptation of Schizothorax to high-salt environments and lay the foundation for future studies on the adaptive mechanism of Schizothorax in the plateau. These results partly fill the void in the knowledge gap in the survival adaptations of Schizothoracine fishes to highland saline lakes.